To the construction of a numerical algorithm for solving the dynamic problems of the theory of discretely reinforced conic shells in a nonorthogonal coordinate system - Meish, V.F.; Meish, Y.A.; Belov, Y.D. (Reports of the National Academy of Sciences of Ukraine, 2019)
The paper deals with the construction of a numerical algorithm for solving the dynamic problems of discretely supported conic shells of an elliptic cross-section under the action of a distributed load on it. The equations of vibrations of a supported conic shell in a nonorthogonal coordinate system and the corresponding numerical algorithm for solving the problems are given. The variant of the theory of shells and rods by the Timoshen ko type is used.